Lean Design Management as a Solution for Delays in Design Phase - B. Harish (International Journal of Architectural Design and Planning, 2024)
The results of this study reveal that traditional project management has a negative impact on the performance of construction projects and addresses its weaknesses in the design stage. Poor quality documentation from poorly managed design projects leads to budget overspending, delay, rework, and disputes. This paper emphasizes the importance of technical cooperation and highlights the lack of focus on value and waste in design development. Lean Design Management (LDM) is suggested as a remedy, emphasizing its unique focus on important components. Through an examination of useful tools and techniques created in the last ten years, the study hopes to add to the continuing discussion on lean design. It aims to talk about how these tools can help with lean design management by improving planning and control during the design process. This study fills in a significant knowledge vacuum and implementing lean principles in design development, offering valuable insights for practitioners and scholars.
Keywords: Design Management; Design delays; Lean Design; Lean techniques/tools